Rotary speed control on Continuous Passive Motion (CPM) Therapy Machine Device with PI Control - Antonius Hendro Noviyanto; Felix Krisna Aji Nugraha; Baskoro Latu Anurogo (Politeknik Negeri Lhokseumawe, 2024)
Continuous Passive Motion (CPM) Machine is a therapeutic device that is used to assist the process of therapy and recovery of a patient after having joint surgeryor injury of the ankle. In this research, a CPM machine will be developed for ankle joint therapy. The rotation speed of the CPM machine will be controlled by a DC motor which is used to drive the ankle joint therapy device.Speed control for DC motor is used on a therapeutic device (CPM machine) to determine the level of the therapeutic process; therefore this device can be adjusted to the needs of the patient who will use the therapeutic device. Speed control of the DC motor that will be carried out in this research is using Proportional Integral (PI) control. With the PI control, the result of output will always be compared with the set point value. The result of this comparison will provide an error value, which later the error value will be processed by PI control.The PI values used in this research are Kp 5 and Ki 15.The test results of the CPM movement speed show that the difference between the set point and the resulting movement is 1 RPM. Where the speed tested on this tool is 3 RPM and 5 RPM. So, the output of this device will be as expected. In brief of this research, a therapeutic device that can be adjusted the rotational speed as expected.